Production of Video Clips by Indigenous Artists - Londoño Proaño, Cristián; Fernando Endara (My University, 2026)
The video clip has been adapted to the digital environment and has gained popularity on platforms such as YouTube. This study analyzes the technocumbia video clips of indigenous artists in Ecuador, using a mixed methodology to observe their production and cultural representation. The findings show that these video clips, in addition to entertaining, serve as commercial vehicles that incorporate indigenous cultural symbols, such as Andean landscapes, traditional dress, and the use of the Kwichua language. The research concludes that these video clips combine tradition and modernity, contributing to cultural self-representation and intercultural communication on the internet
Keywords: Audiovisual production; internet; music video; television; YouTube